2006
DOI: 10.1096/fj.06-5761com
|View full text |Cite
|
Sign up to set email alerts
|

Obscurin modulates the assembly and organization of sarcomeres and the sarcoplasmic reticulum

Abstract: Obscurin (approximately 800 kDa) in striated muscle closely surrounds sarcomeres at the level of the M-band and Z-disk where, we hypothesize, it participates in the assembly of the contractile apparatus and membrane systems required for Ca2+ homeostasis. In this study, we used small inhibitory RNA (siRNA) technology to reduce the levels of obscurin in primary cultures of skeletal myotubes to study its role in myofibrillogenesis and the organization of the sarcoplasmic reticulum (SR). siRNA-treated myotubes sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 45 publications
7
104
2
Order By: Relevance
“…2) (Bowman et al 2007;Fukuzawa et al 2008;Kontrogianni-Konstantopoulos et al 2006;Shriver et al 2015). The specific isoforms of obscurin expressed at these locations is not well established.…”
Section: Diversity Of the Subcellular Distribution Of Obscurinsmentioning
confidence: 99%
See 1 more Smart Citation
“…2) (Bowman et al 2007;Fukuzawa et al 2008;Kontrogianni-Konstantopoulos et al 2006;Shriver et al 2015). The specific isoforms of obscurin expressed at these locations is not well established.…”
Section: Diversity Of the Subcellular Distribution Of Obscurinsmentioning
confidence: 99%
“…Structural and biochemical studies have shown that this complex is necessary for crosslinking thick filaments at M-bands between adjacent myofibrils (Fukuzawa et al 2008;Kontrogianni-Konstantopoulos et al 2004;Kontrogianni-Konstantopoulos et al 2006;Pernigo et al 2015).…”
Section: Obscurins Provide Structural Support For Thick Filaments Andmentioning
confidence: 99%
“…2K), a significant decrease in the diffusion constant and mobile fraction was observed (D of 0.07 Ϯ 0.06 m 2 /s, P Յ 0.01 and M f of 55.9% Ϯ 13.8%, n ϭ 21, P Յ 0.01), indicating that the mobility of ank1.5-GFP became reduced when the protein was organized at the M band. Localization of ank1.5 has been shown to depend on its interaction with obscurin (12)(13)(14)(15)(16). Therefore, to further understand the molecular basis of ank1.5 localization and dynamic properties, an ank1.5-GFP construct mutated in the binding site for obscurin (ank1.5⌬-GFP) was characterized.…”
Section: Dynamics Of Longitudinal Sr Proteins In Primary Skeletal Musmentioning
confidence: 99%
“…Accordingly, immunofluorescence staining of adult skeletal muscle sections has shown that most longitudinal SR proteins, including SERCA pumps and the inositol-trisphosphate receptors (InsP3R), are detected predominantly in correspondence with the Z disk and with a weaker signal over the M band (10). In contrast, the small muscle-specific isoform of ankyrin 1 (ank1.5), a transmembrane protein of the longitudinal SR known to interact with the myofibrillar protein obscurin, is preferentially localized near the M band and, to a lesser extent, to the Z disk (11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Earlier we found that the expression of obscurin gene is rapidly up-regulated during progressive heart hypertrophy (Borisov et al 2003). Downregulation of this protein in cardiac and skeletal muscle resulted in misalignment of myofibrils and multiple defects in the their assembly including the block of proper positioning of myosin filaments Kontrogianni-Konstantopoulos et al 2006;Raeker et al 2006). Thus, understanding of the functional role of obscurin in integration and registered alignment of sarcomeric filaments during myofibrillogenesis will provide new information regarding the mechanisms of assembly and structural support of the myocardial contractile apparatus.…”
Section: Introductionmentioning
confidence: 96%